2013 Learning and Teaching in Computing and Engineering 2013
DOI: 10.1109/latice.2013.19
|View full text |Cite
|
Sign up to set email alerts
|

Computer Science Students' Perception of Computer Network Security

Abstract: Abstract-In the last decade, the progress of internet technologies has led to a significant increase in security and privacy issues for users. This study aims to investigate how computer science students perceive computer network security. Thirty three students participated in the study in which we gathered data through a questionnaire. In this paper, we present an analysis that is inspired by the phenomenographic approach. Our conclusion is that the students have different levels of understanding of computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A survey by Stack Overflow in 2019 showed that 62.4% (75,614 responses) of developers have a degree in CS, computer engineering, or software engineering [60]. Given the importance of this group, many researchers study them to either address gaps between academia and industry [16,37,55,56,61] or to suggest educational tools to improve their skill and abilities [48,62,69]. Research shows that CS students often work under misconceptions which can lead to bad practice.…”
Section: Related Workmentioning
confidence: 99%
“…A survey by Stack Overflow in 2019 showed that 62.4% (75,614 responses) of developers have a degree in CS, computer engineering, or software engineering [60]. Given the importance of this group, many researchers study them to either address gaps between academia and industry [16,37,55,56,61] or to suggest educational tools to improve their skill and abilities [48,62,69]. Research shows that CS students often work under misconceptions which can lead to bad practice.…”
Section: Related Workmentioning
confidence: 99%
“…Mitnick and Simon (2011) pointed out that no matter how technically robust a security technology is, an attacker can breakthrough by exploiting the human element. A cybersecurity mechanism thus can lose its value if users are unwilling to adopt it or cannot use it due to poor usability hence impact negatively on the usability of internet based applications (Cambazoglu and Thota, 2013).…”
Section: Issues Related To the Adoption Of Cybersecurity Controlsmentioning
confidence: 99%